Chassis Ajardinados (Palíndromo, 2013)
This article describes the experiences of producing poetic image in which a thought is expressed about the landscape, more specifically the garden, here conceived as a privileged environment for the questioning of deterministic action that projects designed to advance space occupation have on the landscape. The resulting modeling and standardization suffered by garden areas is highlighted by a process that fracture surface poetic style of landscape. In this sense, the focus is on landscape cliché answer to the problem of cultural hegemonic homogenizing processes, and consequently the formation of modes of subjectivity forged this landscape, while it is wrought by it.
Keywords: garden; flat space; striated space; landscape cliché